Implementing Single-Pill Combination Therapy for Hypertension: A Scoping Review of Key Health System Requirements in 30 Low- and Middle-Income Countries. Issue 1 (25th January 2022) - Bruyn, Eleanor; Nguyen, Long; Schutte, Aletta E.; Murphy, Adrianna; Perel, Pablo; Webster, Ruth
Objective: The World Health Organization (WHO) included single-pill combination (SPC) antihypertensive medications on their 2019 essential medicines list (EML) to encourage uptake and improved hypertension control. We documented key national-level facilitators (SPCs on national EMLs, recommendation for SPCs in national hypertension guidelines and availability of SPCs on the market) supporting uptake of SPCs in the 30 most populous low- and middle-income countries (LMICs). Methods: A hierarchical information gathering strategy was used including literature and web searches, the use of organisational databases and personal communications with colleagues to obtain information on (1) whether SPC antihypertensives are on national EMLs, (2) whether SPC antihypertensives are recommended in national hypertension guidelines and (3) whether SPCs are available on the market. Results: Eleven of 30 LMICs had all facilitators in place being Egypt, Kenya, Nigeria, Sudan, China, the Philippines, Thailand, Iran, Argentina, Colombia and Mexico. Twenty-six countries had national hypertension guidelines (or similar) in place with SPCs being recommended in 18 of these. Apart from Afghanistan, SPCs were available on the market in all countries. The facilitator least present was the inclusion of SPC antihypertensives on national EMLs at 12 of 29 (Turkey does not have an EML). Conclusion: This study demonstrated that many LMICs have made significant progress in their uptake of SPC antihypertensives and several had included SPCs on their EMLs and guidelines prior to their inclusion on the WHO EML. Despite this progress, the uptake of SPC antihypertensives in LMICs could be improved including through their further inclusion on EMLs.